1997
DOI: 10.1017/s0003598x00085860
|View full text |Cite
|
Sign up to set email alerts
|

Fuel for thought? Beeswax in lamps and conical cups from Late Minoan Crete

Abstract: What was burned in lamps in the prehistoric Mediterranean? Olive oil, as one would first suppose? Analysis of absorbed lipids preserved in the fabric of lamps and conical cups from the Minoan site of Mochlos in eastern Crete shows for the first time that beeswax was used as an illuminant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(117 citation statements)
references
References 12 publications
6
107
0
4
Order By: Relevance
“…Dudd and Evershed 1998;Evershed et al 2002;Copley et al 2003;Evershed et al 2008;Dunne et al 2012;Debono Spiteri et al 2016). Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;…”
Section: Introductionmentioning
confidence: 99%
“…Dudd and Evershed 1998;Evershed et al 2002;Copley et al 2003;Evershed et al 2008;Dunne et al 2012;Debono Spiteri et al 2016). Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, beeswax has been regularly detected in later archaeological and historic periods in lipid extracts from the fabric of unglazed pottery vessels 11 where it is assumed to be a residue of honey use in cooking, or from the use of vessels for processing wax combs [12][13][14] , with beeswax being absorbed through repeated contacts. Beeswax has also been detected as a fuel in lamps and in larger vessels used as proto beehives, for example Roman Greece (second century bc to fourth century ad) 15,16 and applied as a post firing treatment to waterproof vessels 17 .…”
mentioning
confidence: 99%
“…The sharp, intense peaks at 2920 and 2850 cm-1 , as well as the absorption at 730-720 cm-1 , are the result of long straight-chain hydrocarbons (e.g., n-alkanes), which are accentuated in the chloroform extracts. Some hydrocarbon absorption, in conjunction with the small peak at 1790 cm-1 and a possible y-Iactone carbonyl absorption in the 1690-1670 cm-1 range, may also be due to an as yet unidentified plant resin or herb, as implied by previous research on ancient Near Eastern wine (McGovern et al 1996.According to gas chromatography-mass spectrometric (GCMS) analysis ( Figure 5b), C 23 H 48 , C 2s H s2 , C 27 H s6 , and C 29 H 6 o-characteristic n-alkanes in beeswax and thus marker compounds of honey (Evershed et al 1997;Xu et al 1989)-possibly account for the straight-chain hydrocarbon IR absorptions. Alternatively, these n-alkanes, with the C 29 compound usually most prominent (Kolattukudy 1976), might be explained by epicuticular waxes, which occur on the surfaces of leaves and fruits of many plants.…”
mentioning
confidence: 73%
“…According to gas chromatography-mass spectrometric (GCMS) analysis ( Figure 5b), C 23 H 48 , C 2s H s2 , C 27 H s6 , and C 29 H 6 o-characteristic n-alkanes in beeswax and thus marker compounds of honey (Evershed et al 1997;Xu et al 1989)-possibly account for the straight-chain hydrocarbon IR absorptions. Alternatively, these n-alkanes, with the C 29 compound usually most prominent (Kolattukudy 1976), might be explained by epicuticular waxes, which occur on the surfaces of leaves and fruits of many plants.…”
Section: T2450mentioning
confidence: 99%